2020
DOI: 10.7189/jogh.10.010802
|View full text |Cite
|
Sign up to set email alerts
|

How to control the economic burden of treating cardio-cerebrovascular diseases in China? Assessment based on System of Health Accounts 2011

Abstract: How to control the economic burden of treating cardio-cerebrovascular diseases in China? Assessment based on System of Health Accounts 2011 Background In the past two decades, chronic non-communicable diseases have become the leading disease burden, and cardio-cerebrovascular diseases (CCVD) are the main causes of death in chronic diseases. It has become the focus of global public health attention, in this study, System of Health Accounts 2011 (SHA 2011) is used to calculate health expenditure, discuss its eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The rapid growth of inpatient services is the main driving force of the growth of medical expenses [15]. According to the regression analysis of the influencing factors of hospitalization expenses, the length of stay is the most important factor, which is consistent with other research results [16]. Logically, the longer the length of hospital stay, the more medical resources will be consumed, which leads to higher hospital costs [17].…”
Section: Discussionsupporting
confidence: 82%
“…The rapid growth of inpatient services is the main driving force of the growth of medical expenses [15]. According to the regression analysis of the influencing factors of hospitalization expenses, the length of stay is the most important factor, which is consistent with other research results [16]. Logically, the longer the length of hospital stay, the more medical resources will be consumed, which leads to higher hospital costs [17].…”
Section: Discussionsupporting
confidence: 82%
“…Chronic diseases have become a global economic burden [27]. Our study revealed that the prevalence of chronic underlying diseases in dead patients with COVID-19 was 72.21% (95% CI 62.85-79.96%).…”
Section: Discussionmentioning
confidence: 71%
“…Then, the ratio is multiplied by the total medical expenses to obtain the total medical expenses of patients with NCDs in Dalian. The specific accounting methods and steps can refer to the previous articles published by our team, and NCDs replaced only the corresponding ICD-10 code 34. All expenditures were converted from reported currencies to 2019 China Yuan.…”
Section: Methodsmentioning
confidence: 99%